Surgical Management of Hepatocellular Carcinoma - Erginöz, Ergin; Dulundu, Ender (Cerrahpaşa Medical Journal, 2025)
Abstract Hepatocellular carcinoma (HCC) is a common primary liver tumor that often develops after chronic liver disease. Main risk factors include hepatitis B and C, alcoholic liver disease, and non-alcoholic steatohepatitis. Despite advances in technology in prevention, incidence and mortality due to HCC continue to rise. Various screening and diagnostic modalities exist, and diagnosis can be established without the need for pathological examination. In the management of HCC, a thorough evaluation of hepatic function is crucial, and various treatment options are available that can be potentially curative. A patient-tailored approach is established in the management of HCC since there are different treatment modalities. These include radiofrequency ablation, transarterial chemoembolization, cryoablation, microwave ablation, radiotherapy, and chemotherapy. Different surgical techniques such as anatomical and non-anatomical resection can also be performed. Although nonsurgical approaches can be used for certain tumors, surgery is often curative, and various classification systems can be used to stratify patients in order to choose a treatment option that is best suited for them. Cite this article as: Erginöz E, Dulundu E. Surgical management of hepatocellular carcinoma. Cerrahpaşa Med J 2025; 49, 0038, doi: 10.5152/cjm.2025.24038